2018
DOI: 10.1111/rec.12874
|View full text |Cite
|
Sign up to set email alerts
|

The good with the bad: when ecological restoration facilitates native and non‐native species

Abstract: Organisms interact with each other along a spectrum ranging from competition to facilitation. A theme in restoration ecology is tipping the balance of these interactions to favor desired species and site conditions, exemplified by restoring fertile islands and their nurse plant effects to encourage plant recruitment. We tested the effectiveness of outplanting nursery-grown native perennials and vertical mulching (placing dead plant material upright in soil) for stimulating annual plant recruitment in a disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
0
16
1
Order By: Relevance
“…This was more often – but not exclusively – the case for growing with a legume compared to growing with a forb or a grass species, which is in line with the positive effect of legume neighbours also found in our models. To date very few studies have found facilitating effects among invasive plants (but see Cushman et al ) whereas more commonly it has been demonstrated that native species can facilitate aliens (Abella and Chiquoine , Lucero et al ). Our results thus highlight that attention has to be raised to facilitative interactions among aliens, especially since they are not limited to benefitting from legumes and occur also in casual neophytes.…”
Section: Discussionmentioning
confidence: 99%
“…This was more often – but not exclusively – the case for growing with a legume compared to growing with a forb or a grass species, which is in line with the positive effect of legume neighbours also found in our models. To date very few studies have found facilitating effects among invasive plants (but see Cushman et al ) whereas more commonly it has been demonstrated that native species can facilitate aliens (Abella and Chiquoine , Lucero et al ). Our results thus highlight that attention has to be raised to facilitative interactions among aliens, especially since they are not limited to benefitting from legumes and occur also in casual neophytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, Abella and Chiquione (2018) recently showed that efforts to use positive interactions to restore native biodiversity benefitted exotic species more than native species. Similarly, we found that shrub-mediated interactions greatly benefitted B. rubens but not the native annual community, underscoring the potential for strong facilitation of invasive species to confound restoration efforts.…”
Section: Ta B L Ementioning
confidence: 99%
“…In changing drylands, positive interactions can benefit exotic plant species more than their native competitors (Abella & Chiquione, 2018). For instance, Lucero et al (2019) monitored associations between native shrubs and the annual plant communityincluding native and exotic taxa-over three years in a California desert and found that shrubs facilitated the abundance of exotic annual species 2.75 times stronger than native annual species.…”
Section: Introductionmentioning
confidence: 99%
“…In northern Arizona, we found that biotic resistance to B. tectorum invasion is both functional group-specific and species-specific. Although enhancing resistance can be challenging in largely uninvaded systems (e.g., Abella and Chiquoine 2019;Pierson et al 2007), our results indicate that high-rate broadcast seeding can produce native perennial grass seedlings that quickly begin suppressing B. tectorum abundance in these systems. A targeted two-week spring grazing treatment of 30% utilization (20 animals across 20.2 ha; 13.9 AU Days per ha) did not negatively affect measured outcomes and had several potentially positive, but uncertain outcomes, including increased seedling densities in planted plots and decreased B. tectorum biomass in low seeding rate treatments.…”
Section: Discussionmentioning
confidence: 77%
“…resource inputs and manipulations of plant communities via seeding, herbicide, targeted grazing, or other methods) may be useful for increasing biotic resistance within lightlyinvaded systems (e.g., Munson et al 2015). However, active restoration may be risky in largely intact arid ecosystems, since many common methods could lead to soil erosion, damage to desired species, further invasion, or other unintended consequences (e.g., Abella and Chiquoine 2019;Diamond et al 2012;Owen et al 2011;Pierson et al 2007;Porensky et al 2018).…”
Section: Introductionmentioning
confidence: 99%